Estado nutricional, nível de atividade física, circunferência de cintura e flexibilidade em meninos brasileiros - Fernandes, Rômulo Araújo; Destro Christofaro, Diego Giuliano; Grizzo Cucato, Gabriel; Agostini, Lucas [UNESP]; de Oliveira, Arli Ramos; Freitas Júnior, Ismael Forte [UNESP] (My University, 2007)
This study examined the relationships between nutritional status, physical activity, waist circumference, and flexibility in boys. The sample comprised 74 boys (11,8 years old, SD= 1,6). The following were measured: body weight, height, waist circumference, physical activity, body fat (bioelectrical impedance) and flexibility. Body fat percentage was calculated, and the children were classified as well nourished (G1), overweight (G2), or obese (G3) according to the age and sex adjusted cutoffs described by Taylor et al.18. The statistical procedures adopted were: mean, standard deviation, analysis of variance, chi-square test, linear correlation and binary logistic regression. The level of significance was set at p < 0.05. There was a statistical difference between G3 and G1 in flexibility scores (p = 0.048). Obese and inactive boys were more than twice as likely to exhibit a poor flexibility score than well nourished and active boys, respectively (odds ratio= 2.9; p = 0.046, and 5.1; p = 0.047, respectively). This study identified the existence of relationship and association between obesity, physical inactivity and poor performance in flexibility test.
Nutritional status, physical activity level, waist circumference, and flexibility in brazilian boys
Keywords: Body fat; Flexibility; Physical activity; Waist circumference